Children in Digital Age – Romanian Perspective - Kokoly, Zsolt (Children in Digital Age, 2025)
Abstract:The paper conducts a detailed analysis of children’s rights in Romanian legislation with a special focus on their application in a digital context. As the study shows, Romania does not have extensive legislation concerning children’s rights in the digital environment, and thus one of the main challenges of the study is identifying the relevant sources of law among the more general pieces of legislation and adjusting them to the digital environment. The study is structured in six chapters, where the introductory chapter presents the general legislative framework on the rights of the child in Romania, including a brief historical overview of the main milestones of the development of children’s rights, concluding with an outline of the most important rights and categories of rights children enjoy according to the international and Romanian legislation. The next chapters proceed with the analysis of six different topics, namely, the protection of children against digital harm based on the Romanian Criminal Code and the National Education Law, the review of authorities entrusted with the protection of children’s rights in the digital world, the protection of children by the media law, the right of the child to be informed, heard, and express their opinion, aspects related to data protection, and finally, the state of play of the protection of children’s rights in Romania’s digital space. Keywords: children, Romania, children’s rights, digital environment, digital harm, media law, data subjects, freedom of opinion